Diagnostic Performance of Shear Wave Elastography in the Noninvasive Evaluation of Liver Inflammation of Chronic Hepatitis B Patients. Issue 2 (June 2021) - Ren, Xinping; Zhang, Lu; Xia, Shujun; Zhou, Jianqiao; Lin, Yanyan; Zhijie, Chen; Li, Ruokun; Zhan, Weiwei
Abstract : Abstract: In the current study, we sought to delineate the elastographic characteristics and further compare the diagnostic performance of various shear wave elastography modalities in hepatitis B virus patients whose liver fibrosis stage was less than F2 by liver biopsy. We retrospectively studied the clinical and imaging data of chronic hepatitis B virus patients who underwent liver biopsy at our hospital between January 2017 and October 2017. Totally, 102 patients were eligible for the study. The mean Young modulus of sound touch elastography (STE) and sound touch quantify (STQ) gradually increased as inflammation grade of the liver rose from G0 to G3. Spearman rank correlation analysis revealed that the mean Young modulus of STE and STQ significantly correlated with hepatic inflammation grade ( r = 0.341, P < 0.05). The area under the receiver operating characteristic curve (AUC) was the highest for the mean Young modulus of STE (AUC = 0.740; P = 0.015) followed by that of STQ (AUC = 0.684; P = 0.063) for G ≥ 2 hepatic inflammation and the AUC was the highest for the mean Young modulus of STE (AUC = 0.920; P = 0.000) followed by that of STQ (AUC = 0.910; P = 0.000) for G ≥ 3 hepatic inflammation. The current study demonstrated that the mean Young modulus of STE and STQ could serve as a useful diagnostic marker for hepatic inflammation of hepatitis B virus patients with no apparent liver fibrosis.